Strengthening local food production and trade in the Caribbean: Stories from the field - Pye-Smith, Charlie (Technical Centre for Agricultural and Rural Cooperation, 2017)
Governments, the private sector, and small-scale farmers all have an important role to play when it comes to increasing home-grown food production, and the stories told in this booklet provide an insight into a variety of projects and programmes that are helping Caribbean islands to become more self-sufficient.